Micropartículas de metotrexato e ácido poli lático-co-glicólico obtidas por “spray-drying” - Garcia, Mirela Cardoso [UNESP] (2014)
Methotrexate (MTX) is an antineoplastic agent of a short half-life, poorly soluble in water, alcohol, ether and chloroform, which affects your bioavailability. Poly lactic acid-co-glycolic acid (PLGA) is a biodegradable polymer that is hydrolyzed in the body, often used in controlled release system because of your characteristics the degradation. Microparticles PLGA / drug obtained by spray drying have been used in various pathologies, including anterior and posterior segment of the eye diseases. The aim of this study was to develop and characterize PLGA microparticles containing MTX obtained by spray-drying for a potential intraocular administration. PLGA microparticles containing MTX at two different concentrations were obtained. The morphology of the microparticles was spherical and the more drug is added, the particle tends to deform and the drug to be deposited on the particle surface. The infrared analysis (FTIR) suggest the occurrence of a physical mixture of PLGA and MTX, probably the interaction between carboxylic acids and amines present in MTX and the esters in PLGA molecule. The differential scanning calorimetry (DSC) and X-ray diffraction result that MTX is dispersed in the polymeric matrix with the prevalence of amorphous state, favoring the encapsulation efficiency (greater than 80%) and release, where PLGA microparticles containing 10% MTX showed sustained release profile after 72 hours, while containing 50% MTX characterize an initial burst effect and a slower release. The experimental results concludes successfully in obtaining microparticles PLGA containing MTX by spray drying and its potential as sustained drug release system may be interesting in treatment of eye diseases.